USE OF STORYMAP IN DISASTER MITIGATION BASED ON LOCAL WISDOM (Case Study: Sapuran District, Wonosobo Regency, Central Java) - Dessy Apriyanti; Celine Tracyana; Fauzan Zaidan (Universitas Pembangunan Nasional (UPN), 2024)
Wonosobo, known for its highland topography and significant tourism potential, stands out as a region deeply enriched by local wisdom and strategic location, which has earned it the moniker